The Metal Finds from Pyla-Vigla: An Early Hellenistic Fort in Southern Cyprus - DiFabio , Christina; Olson , Brandon R.; Landvatter , Thomas; Stephens , Justin (Journal of Hellenistic Pottery and Material Culture, 2024)
The death of Alexander the Great in 323 BCE cast a great shadow of uncertainty throughout the Eastern Mediterranean in the absence of a clear path to successorship. The epitome of an autonomous leader, Alexander did little to share his authority but surrounded himself with the strongest, most capable leaders that Greece and his newly acquired lands had to offer. It was this approach to leadership and those individuals that both proved integral to the success of his campaigns and led to one of the most disruptive eras of the ancient world. Furthermore, Alexander’s imperial policies following the subjugation of any given area often mimicked the political structure of the former entity. Those regions previously subject to the Achaemenid Persian Empire continued a system of satrapies, where Alexander replaced local satraps with an ally. The eastern provinces, especially around the Indus River Valley, maintained a kingdom-oriented organization with a monarch of Alexander’s choosing. While one can argue the degree to which Alexander created a centralized empire after the conclusion of his campaigns in 326 BCE, it is clear that the continuation of such an entity was simply impossible. Alexander’s realm was in its infancy and required regular interventions against local uprisings and reassertions of authority to maintain control. It was at this juncture that his former generals devised a minimum of three separate plans in 323 BCE, 320 BCE, and 311 BCE to stabilize the empire. All three documented partitions named a king (or soon to be king), a regent, and divided the realm into satrapies or regions governed by a formal general or ally. The plans paved the way for either Alexander’s son (Alexander IV) or his half-brother Arrhidaeus (Philip III) to become the sole legitimate heir of Alexander the Great and provide the long-term answer to dynastic succession and stability. These plans, however, never materialized. The assassinations of Philip III (Alexander’s half-brother) in 317 BCE, Olympias (Alexander’s mother) in 316 BCE, and Roxane (Alexander’s wife) and Alexander IV (Alexander’s son) in 310 BCE ended the Argead Dynasty and any hopes of a singular ruler taking over Alexander’s great empire.